2015
DOI: 10.1590/0103-6440201300294
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Universal, Self-Etching and Etch-and-Rinse Adhesive Systems According to the Polymerization Time

Abstract: This in vitro study evaluated in fibroblast cultures the direct cytotoxicity of universal, self-etching and etch-and-rinse adhesive systems according to the polymerization time. Paper discs were impregnated with adhesives and light-cured (10, 20 or 40 s). The discs were then immersed in culture medium to obtain the eluates for the experimental groups (A1-Single Bond 2; A2-Scotchbond Multi-purpose; A3-Clearfil SE Bond; A4 Scotchbond Universal). As a negative control, paper discs were immersed in culture medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
4
32
1
5
Order By: Relevance
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Contradictory, other studies found that Etch-and-Rinse adhesives were more cytotoxic [11,17,[20][21][22][23][24][25]. However, in all of the comparative studies, other methods, materials and their combinations were used [11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It should be noted that in the clinical application of Etch-and-Rinse adhesives conditioning with 37% phosphoric acid is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature increase was influenced by the light source, and the LED with high irradiance caused higher heating compared to QTH light and low LED, confirming the results obtained in other study (3). This may be due to the fact that the LED emits more specific wavelengths, closer to the absorption spectrum camphorquinone (17), often having a polymerization performance equal to or better than the QTH light (18). However, other authors comparing temperature changes with different photo-activation methods concluded that the QTH light source produced higher temperatures when compared to LED and Plasma Arc light sources (19).…”
Section: Discussionsupporting
confidence: 85%